(A) 3+2(x-1)
3+2x+2
2x+5
(B) 5-2(x+3)
5-2x-6
-2x-1
(C) 1+2(x-1)
1+2x-2
2x-1
(D) 6-3(w-2)
6-3w+6
-3w+12
2006-11-02 05:33:06
·
answer #1
·
answered by Brian 3
·
0⤊
0⤋
Hello Anna
I am delighted that I can help you out with your questions
Would be so grateful if anyone can help me with these math problems?
Multiply out then simplify:
a- 3+2(x-1) = 3 +2x -2 = 2x+1 = 3
b- 5-2(x+3) = 5 -2x -6 = -1-2x = -3
c- 1+2(x-1) = 1 +2x-2 = -1+2x = 1
d- 6-3(w-2) = 6 - 3w + 6 = 12-3w = 9
God Bless You
2006-11-02 13:51:21
·
answer #2
·
answered by ramesh the great 1
·
0⤊
1⤋
a- 3+2x -1
b- 5 -2x -6
c- 1 +2x -2
d 6-3w +6
eg- 3 +2(x-1) you must work out the brackets to simplify 2 x X & 2 x -1 = 3 + 2x -1
2006-11-02 13:36:16
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
3+2(x-1) = 3 + 2x - 2 = 1 + 2x
5-2(x+3) = 5 - 2x + 6 = 11 - 2x
1+2(x-1) = 1 + 2x - 2 = -1 + 2x
6-3(w-2) = 6 - 3w - 6 = 0 - 3w = -3w
2006-11-02 13:38:53
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
I'll do one to show you how it's done.
6-3(W-2)
3(W-2) means you muliply each term in the ()'s by the number outside of it so:
3(W-2) gets turned into 3W + 6
Now you have the problem
6-3W + 6
Combine like terms so what is 6 +6? 12 right? So you end up with -3W + 12
2006-11-02 13:35:48
·
answer #5
·
answered by Roman Soldier 5
·
0⤊
0⤋
I don't understand what you are asking for !!!
are these equations where you are asked to find the value of x? if so, then you must show the other side.
If you are only asking to make it look simple, then let me try a
3 + 2(x-1)
3 + (2x - 2) simply it becomes
3 + 2x - 2
1 + 2x
and for the rest
b - 1 + 2x
c - 2x - 1
d - 12 - 3w
I hope i got your point
goodluck
2006-11-02 13:39:07
·
answer #6
·
answered by Alessandro84 2
·
0⤊
0⤋
a- 3+2(x-1) = 3+2x-2 = 2x+1
b- 5-2(x+3) = 5-2x-6 = -2x-1
c- 1+2(x-1) = 1+2x-2 = 2x-1
d- 6-3(w-2) = 6-3w+6 = 12-3w
2006-11-02 13:32:41
·
answer #7
·
answered by Vladimir S 2
·
0⤊
0⤋
a) =3+2x-2
=1+2x
2x=-1 so x= -1/2
b) = 5-2x-6
= 5-6-2x
= -1-2x
-2x=1 so x=1/2
c) = 1+2x-2
= -1+2x
2x=1 so x= -1/2
d) =6-3w+6
=-3w so w=3
2006-11-02 15:29:57
·
answer #8
·
answered by boulonpitou 2
·
0⤊
0⤋
you work out the sum, then add the backet
so a)3+2(x-1)=5+x-1
=4+x
2006-11-02 13:35:53
·
answer #9
·
answered by siany warny 4
·
0⤊
1⤋
i will do one,
3+2(x-1)
3+2x-2<---- distribute you 2 by multiplying all things in the () by 2
1+2x <--- combine like terms..bam your done
2006-11-02 13:31:38
·
answer #10
·
answered by ashley 3
·
0⤊
0⤋